Child social isolation cases in Malaysia: A plan of action for stakeholders - Fansuri, Mohd Faiz; Azman, Azlinda (Southeast Asia Early Childhood Journal, 2022)
Most cases of child social isolation began with the child gone missing from society. Although being a missing child is not an indicator of being socially isolated, it can lead to becoming one. Based on Royal Malaysian Police statistics, over 4, 400 children have been reported missing from 2017 to 2021, which may lead to a growing number of socially isolated children in Malaysia. Therefore, upon better comprehension of this phenomenon, rescued children can be assisted in adaption and re-integrated into society. This study is designed to explore the experiences including feelings, thoughts, needs and behaviour of Malaysian socially isolated children. In achieving this, the primary methods of collecting data are systematic observation and in-depth interviews. These activities were conducted at a local child social welfare institution. Out of 123 children observed, six (6) children aging from three (3) to eight (8) years old were identified as socially isolated and interviewed either directly or through informants. Thematic analysis revealed socially isolated children have difficulties in areas of self-concept, attachments, and social interactions. In addition, the study found that factors causing child social isolation were dysfunctional family, unsafe environment, and limited resources.